(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Higher education institutions are one of the decisive links in popularizing and developing sports among women in Uzbekistan. In particular, in higher educational institutions, measures were taken on the basis of a permanently defined plan for the training of female coaches, the organization of various sports clubs for female students, and their preparation for competitions.